DOI: 10.18130/v3xw0n
|View full text |Cite
|
Sign up to set email alerts
|

Affective Processing Following Romantic Relationship Dissolution

Abstract: This study prospectively examined the emotional experiences of 58 young adult college students who had, within the previous two weeks, ended a committed romantic relationship lasting an average of 20 months. Participants completed an intake questionnaire battery and then rated their emotional experiences in a daily diary when signaled at random each day for 28 days. After the month period, participants were re-assessed with the same intake questionnaire materials. The chief aims of this study were to prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(175 reference statements)
0
1
0
Order By: Relevance
“…In addition, anxiously attached individuals were found to have hyperactive affect-regulation in order to intensify their expressed distress, whereas avoidantly attached individuals reduced their expressed distress by deactivating their affect-regulation (Ponizovsky & Drannikov, 2013) Similar to the results in the Western culture, several local studies also suggest a positive relationship between secure and preoccupied attachment style, and social support seeking (Krawcomsri, 2002). Research also found that dispositional emotion coping, secure attachment, and anxious attachment were predictive of increased state depression, while perceived control and avoidant attachment were negatively related to depression (Speer, 1997).…”
Section: Coping Strategiesmentioning
confidence: 91%
“…In addition, anxiously attached individuals were found to have hyperactive affect-regulation in order to intensify their expressed distress, whereas avoidantly attached individuals reduced their expressed distress by deactivating their affect-regulation (Ponizovsky & Drannikov, 2013) Similar to the results in the Western culture, several local studies also suggest a positive relationship between secure and preoccupied attachment style, and social support seeking (Krawcomsri, 2002). Research also found that dispositional emotion coping, secure attachment, and anxious attachment were predictive of increased state depression, while perceived control and avoidant attachment were negatively related to depression (Speer, 1997).…”
Section: Coping Strategiesmentioning
confidence: 91%